2004
DOI: 10.1007/s00125-003-1292-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac repolarization during clinical episodes of nocturnal hypoglycaemia in adults with Type 1 diabetes

Abstract: Aims/hypothesis. Experimental hypoglycaemia leads to abnormal cardiac repolarization manifest by a lengthened QT interval and caused by adrenergic stimulation. However it is less clear whether spontaneous clinical episodes lead to similar changes. We have therefore measured cardiac ventricular repolarization and counterregulatory responses in patients with Type 1 diabetes during hypoglycaemic and euglycaemic nights. Methods. We studied 22 patients with Type 1 diabetes (mean age 40.4±17.2 years, duration of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 19 publications
(20 reference statements)
3
83
1
2
Order By: Relevance
“…Conversely, other studies have reported that abnormal autonomic function at this age [33,34,35,36,37] is largely related to hyperglycaemia and elevated HbA 1 c. However, our data strongly indicate that spontaneous hypoglycaemia rather than hyperglycaemia is the more important determinant of prolonged QTc at night in type 1 diabetic children and adolescents. We have recently demonstrated similar changes during hypoglycaemia in adults [38]. We chose a glucose level of 3.5 mmol/l to define hypoglycaemia as previous studies carried out by our group in children and adolescents demonstrated that levels in normal children almost never go below this value.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, other studies have reported that abnormal autonomic function at this age [33,34,35,36,37] is largely related to hyperglycaemia and elevated HbA 1 c. However, our data strongly indicate that spontaneous hypoglycaemia rather than hyperglycaemia is the more important determinant of prolonged QTc at night in type 1 diabetic children and adolescents. We have recently demonstrated similar changes during hypoglycaemia in adults [38]. We chose a glucose level of 3.5 mmol/l to define hypoglycaemia as previous studies carried out by our group in children and adolescents demonstrated that levels in normal children almost never go below this value.…”
Section: Discussionmentioning
confidence: 98%
“…Both these conditions are possibly linked to cardiac autonomic neuropathy and prolonged QT interval. In experimental and in spontaneous nocturnal hypoglycaemia, prolongation in QTc has been demonstrated [32,33], and pre-treatment with a beta blocker demonstrably prevented abnormal repolarisation during experimental hypoglycaemia [32]. We have previously shown that it is possible to improve heart rate variability parameters by B1-selective beta blockade [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that intensification of glucose and blood pressure management may increase the risk of a cardiovascular event in people with signs of CAN (161)(162)(163)(164)(165). Similarly, emerging evidence demonstrates an association between CAN and glucose variability, especially in the hypoglycemic range (150,164).…”
Section: Canmentioning
confidence: 99%